PENENTUAN KADAR NAFKAH IDDAH DAN NAFKAH MUT’AH PASCA PERCERAIAN PADA MASA PANDEMI COVID-19 DI PENGADILAN AGAMA SIDRAP - Mutmainna; Kasjim Salenda; Hamzah Hasan (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main problem of this research is how to determine the levels of iddah and mut'ah maintenance after divorce during the Covid-19 pandemic at the Sidrap Religious Court (case study on decision no. 251/Pdt.G/2021/PA.Sidrap). This research is a type of field research with a legal approach. The results of this study indicate that the view of Islamic law regarding iddah and mut'ah maintenance is seen on the basis of articles 149, letters a and b, and 151 of the Compilation of Islamic Law. In addition, in determining the levels of iddah, mut'ah, and children, the judge has considered the sense of justice and propriety by examining the economic capacity of men and the facts of the basic needs of his wife and children.